2019
DOI: 10.1007/s40199-019-00242-x
|View full text |Cite
|
Sign up to set email alerts
|

Proniosomal gel for transdermal delivery of lornoxicam: optimization using factorial design and in vivo evaluation in rats

Abstract: Objective Clinical utility of lornoxicam in oral therapy is primarily restricted by the low solubility and gastric adverse effects. This study evaluated the prospective of optimized proniosomal gel to improve the clinical efficacy of lornoxicam and compare with oral therapy. Methods Proniosomes were formulated by coacervation phase separation technique using span 60, lecithin and cholesterol. A four-factor three-level Box-Behnken design was used to evaluate the effect of amount of four independent variables; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…However, both the hydrogel TNX-NLCs and the oral TNX were guarded against these changes to roughly the same extent. Similar findings were reported by other authors (Goindi et al., 2016 ; Baranowski et al., 2018 ; Shah et al., 2019 ). Although the present study did not measure the pharmacokinetics of the drug, our findings suggested that TNX-NLCs hydrogel reached the dermis of the skin and then passed into the systemic circulation and showed its anti-inflammatory effect almost similar to the oral TNX by decreasing the production of free radicals and pro-inflammatory mediators that were accelerated 3 h after carrageenan inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…However, both the hydrogel TNX-NLCs and the oral TNX were guarded against these changes to roughly the same extent. Similar findings were reported by other authors (Goindi et al., 2016 ; Baranowski et al., 2018 ; Shah et al., 2019 ). Although the present study did not measure the pharmacokinetics of the drug, our findings suggested that TNX-NLCs hydrogel reached the dermis of the skin and then passed into the systemic circulation and showed its anti-inflammatory effect almost similar to the oral TNX by decreasing the production of free radicals and pro-inflammatory mediators that were accelerated 3 h after carrageenan inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in droplet size with increase oil% in the formulation might be explained by the fact that increase ratio of oil to Smix is reflected by reduction of interfacial tension between the interface of two immiscible liquids. Additionally, the inverse relation between percentage of Smix and droplet size can be explained by the fact of that increased Smix% helps in reducing interfacial tension between oil and aqueous phase and thereby provides successful coating over the nano droplets which further leads to stabilization of the developed NEs [ 40 ]. These findings are in agreement with reported literatures [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has potential gastrointestinal, liver, cardiac and renal toxicities. 9 Many approaches were previously used to overcome the side effects of LX such as liposomes, 9 proniosomal gel, 10 and niosomes. 11 Transdermal delivery system provides an approach to avoid the side effects of NSAIDs and extend duration of action.…”
Section: Introductionmentioning
confidence: 99%